Reactive balance responses to an unexpected slip perturbation in individuals with incomplete spinal cord injury. (August 2020) - Arora, Tarun; Musselman, Kristin E.; Lanovaz, Joel L.; Linassi, Gary; Arnold, Catherine; Milosavljevic, Stephan; Oates, Alison
Abstract: Background: Frequent falls while walking among individuals with incomplete spinal cord injury may suggest impairments in reactive balance control; however, reactive balance control during walking has not been studied in this population. The objective was to compare reactive balance control with respect to changes in margin of stability, onset of arm and heel responses, and onset and magnitude of muscle activity following an unexpected slip perturbation in individuals with incomplete spinal cord injury and able-bodied individuals. Methods: Kinematic and electromyography data were obtained during normal walking and one unexpected slip. Changes in margin of stability following a compensatory or aborted step, onset of arms and trail heel responses, and onset and magnitude of activation of the tibialis anterior, soleus and gluteus medius were calculated. Multivariate analyses compared responses between incomplete spinal cord injury and able-bodied groups. Findings: Data from 16 participants with incomplete spinal cord injury (all American Spinal Injury Association Impairment Scale Grade D, 8 with tetraplegia) and 13 age-and-sex matched able-bodied individuals were included. Individuals with incomplete spinal cord injury demonstrated limited ability to increase margin of stability in the lateral direction during a compensatory or aborted step, and a smaller magnitude of soleus activity compared to able-bodied individuals. Interpretation: There are limitations in reactive balance control of individuals with incomplete spinal cord injury, which may be a reason for the high frequency of falls in this population. Reactive balance assessment should be included as a component of routine balance assessment and fall avoidance strategies in this population. Highlights: Ability to react to unexpected slip is impaired after incomplete spinal cord injury. Ability to increase sideways margin of stability using a step is limited. Magnitude of non-slip side soleus muscle activity is smaller. Other reactive responses are comparable to able-bodied individuals.